Alteraciones clínicas de la mucosa bucal en personas de la tercera edad portadoras de prótesis totales - Sotomayor Camayo, Justiniano (2002)
57 adults of the third age that worn Complete prosthesis were examined in the residence of "Hermanitas de los Ancianos Desamparados" in Breña, Lima, Perú; 29 of them were men and 28 women. The age of those examined went from 65 to 94 years old, with a mean of 79. A clinical evaluation of the buccal cavity was made as well as evaluation of the prosthesis state in use. It was, determined that 73,7 %, presented clinical alterations in the buccal mucous associated to the use of complete prosthesis. The alterations more frequently presented were: subplaque stomatitis in 33,3 %; traumatic ulcer in 21,4 %; hyperplasia in 16,7 %; leukoplakia in 11,9 %; angular Cheilitis in 9,5 %; and seudomembranous candidosis in 7,1 %. The time of use of the prosthesis influenced significantly in the presentation frequency of mucous alterations. At more time of use the alterations more frequently presented were: subplaque stomatitis, hyperplasia, angular cheilitis and seudomembranous candidosis. In the first five years of wearing the most frequent lesion was traumatic ulcer. The complete prosthesis adaptation state influenced significantly in the presence of mucous alterations. The use of "disadapted prosthesis" was basically associated with: hyperplasia, angular cheilitis and traumatic ulcer.